Spray Performance Case Study of an Agriculture Drone in Pineapple Plantation - Wan Jamaludin, Wan Akashah; Mohd Faizan Marwah @ Omar, Omar; Rahim, Muhammad Zulafif; Mohd Saleh, Siti Juita Mastura; Hassan, Suhaimi; Mohamad, Elmy Johana (2024)
The quality of spraying or efficacy is important in agriculture as it impacts the environment and the cost of operation. Over-application of a product will affect the surrounding area, leading to runoffs and wastage. Plants require a specific amount of product for optimum growth, which applies to fertiliser and herbicide use included in this study. A case study at a pineapple plantation was conducted, referencing both the product direction of use and feedback from the farmers at the plantation based on the agriculture strategies practised. Using a quadrotor drone with a 16-litre capacity with two types of nozzles (flat and cone) for the herbicide and fertiliser application with flight parameters of 2 meters in height and 2-4 m/s flight speed resulted in a coverage of 20-30 L/acre. Documentation of the practice is recorded here for reference to the practice in Malaysia's pineapple plantation.